2021
DOI: 10.1112/s0010437x20007691
|View full text |Cite
|
Sign up to set email alerts
|

An arithmetic count of the lines on a smooth cubic surface

Abstract: We give an arithmetic count of the lines on a smooth cubic surface over an arbitrary field $k$ , generalizing the counts that over ${\mathbf {C}}$ there are $27$ lines, and over ${\mathbf {R}}$ the number of hyperbolic lines minus the number of elliptic lines is $3$ . In general, the lines are defined over a field extension $L$ and have an associa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 30 publications
(19 reference statements)
1
37
0
Order By: Relevance
“…(c.f. [OT14], [KW21], [Mor12, §4.3]) Suppose E → X is a vector bundle of rank n over a smooth, projective n-scheme over a field k. Then we say E is relatively oriented over X if there is an isomorphism…”
Section: 4mentioning
confidence: 99%
“…(c.f. [OT14], [KW21], [Mor12, §4.3]) Suppose E → X is a vector bundle of rank n over a smooth, projective n-scheme over a field k. Then we say E is relatively oriented over X if there is an isomorphism…”
Section: 4mentioning
confidence: 99%
“…For a relatively oriented vector bundle V equipped with a section with only isolated zeros, an Euler number was defined in [49, Section 4] as a sum of local indices: The index can be computed explicitly with a formula of Scheja and Storch [67] or of Eisenbud and Levine/Khimshiashvili [29] (see §§2.4 and 2.3) and is also a local degree [48] (this is discussed further in §7). For example, when x is a simple zero of with , the index is given by a well-defined Jacobian of , illustrating the relation with the Poincaré–Hopf formula for topological vector bundles.…”
Section: Introductionmentioning
confidence: 99%
“…(For the definition of the Jacobian, see the beginning of §6.2.) In [49, Section 4, Corollary 36], it was shown that when and are in a family over of sections with only isolated zeros, where L is a field extension with odd. We strengthen this result by equating and ; this is the main result of §2.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations